Dampak Pandemi Covid-19 terhadap Perubahan Perilaku Keuangan pada Generasi Milenial selama Masa Pandemi Covid-19 di Indonesia - Rika Persada; Ni Kadek Sinarwati (Syntax Idea)
The spread of Covid-19 in Indonesia has caused disruption in all sectors, including the economic sector. One of the economic sectors that is currently in the spotlight is the declining per capita income, while consumption must continue to fulfill daily life. This article aims to determine the financial behavior of Indonesian people before and after the Covid-19 pandemic. Apart from that, it also measures whether there are differences in the financial behavior of Indonesian people before and after the Covid-19 pandemic, so that it can be a reference for what financial behavior should look like. The impact of the Covid-19 pandemic is of course a force majeure situation that can occur anytime and anywhere. As a generation that is in a productive age, the millennial generation is a generation that has a significant role in controlling the wheels of development in Indonesia, especially in the economic field. But unfortunately, the millennial generation is also known as a very wasteful generation because of its lifestyle. The emergence of a pandemic then affects the community’s economic conditions, including the millennial generation. This article found that millennials could reduce their wasteful nature during the pandemic and allocate their funds for more urgent and adaptive needs. Then the impact of the pandemic also provides better financial literacy for the millennial generation on their financial management behavior